Low molecular weight heparin prophylaxis: a boon for women with history of placental mediated complications - Singh, Shweta; Sinha, Renuka; Kaushik, Mayank (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prevention of placental mediated pregnancy complication is likely the best approach to decrease maternal mortality and morbidity. Anticoagulation therapy represents a good preventive option. Methods: A prospective randomized case control study was conducted at Safdarjang hospital. Patients were recruited from Sept. 2011 till May 2012 and followed till delivery. Thirty cases & controls were enrolled which comprised of non- thrombophilic patients with previous history of severe preeclampsia, Fetal Growth Restriction (FGR), severe placental abruption, stillbirth after 20 weeks. Study group received LMWH according to weight subcutaneously, once daily started at < 15 weeks till 36 weeks of gestation. Maternal outcomes were observed in both groups. Results: Incidence of stillbirth and abruption were significantly lower in study group (0 versus 3.3%, P = 0.05; and 0 versus 20%, P = 0.01). The respective incidence of severe preeclampsia and FGR were 6.6% versus 40% (P = 0.04) and 6.6% versus 30 % (P = 0.02). There was reduction of 72.7% of total adverse outcome. Conclusions: Prophylactic LMWH before 15 weeks of gestation decreases the incidence of placental mediated complications in non thrombophilic pregnant women who had previously suffered with these complications.